Implementing programmatic assessment transforms supervisor attitudes: An explanatory sequential mixed methods study. (3rd June 2021) - Jamieson, Janica; Hay, Margaret; Gibson, Simone; Palermo, Claire
Abstract: Introduction: Programmatic assessment (PA) is an increasingly popular approach to competency-based assessment (CBA), yet evaluation evidence is limited. This study aimed to identify and explore supervisor attitudes before and after implementing a novel PA using a sequential explanatory mixed methods design. In phase one, a survey was used to identify supervisor perspectives on work-based placements, PA and CBA. Survey results were then applied to develop focus group questions to further explore supervisor attitudes. Results: PA was found to improve supervisor-student relationships by removing high-stakes assessment decisions and creating greater capacity for feedback and teaching, leading to a productive learning environment. Assessment was perceived as an important role and supervisors wanted to feel valued and heard within PA. Trust was conceptualised as a triad between supervisor, student and university, and enabled supervisors to engage with PA which was important for success. Supervisor learning of PA was experiential and often supported by students, highlighting the need for hands-on training. Conclusion: Participants reported a high level of agreement with PA and CBA principles which may have made them amenable to educational change. Further research is needed to explore the experience of all stakeholders and to understand how worldviews and culture influence assessment initiatives.